Design of Catamaran Ship Using Solar Power - Ramadhan, Ozi; Syahril, Syahril; Nurdin, Hendri; Purwantono, Purwantono (Universitas Negeri Padang, 2019)
Solar power is a renewable energy that can replace oil fuel as the main energy of the ship. The use of fuel oil can worsen the environment in the Maninjau lake tourism area. This paper aims to develop a ship propulsion design using solar power with the main size of the WL bilge Length 367.33 cm, Width (B) 170 cm, Height (H) 70 cm, Draught (T) 30.7 cm. To produce the power needed at a speed of 6 knots, using the method of theoretical analysis by counting, total energy and solar panels to convert sunlight into electrical energy. The result of calculating the total energy needed to reach 6 knots is 0.932 kW. The solar panels needed to produce the power are 4 pieces with a capacity of 100 Wp. This system does not use an inverter because it uses a DC electric motor as a vessel driver. The design of a solar-powered boat can be an option for the community as an environmentally friendly tourist ship without fuel.